A Study on the Psychological Network of Wellbeing in Japanese Language Learners Based on the PERMA Model: A Psycholinguistic Perspective - Wei, Fang (Forum for Linguistic Studies, 2025)
This study examines the study of the Japanese language in China. It employed a psycholinguistic approach, utilising the theoretical framework of PERMA. The study participants (N = 226) were all Japanese majors aged 18 to 22 years from three universities in Central China. The learners also completed a modified PERMA Profiler and a Negative Emotion subscale, which consider both positive and negative aspects of a person’s state concerning psychological functions. The descriptive results indicated that the overall well-being of the students was in the upper-middle range. Among the five PERMA dimensions, Meaning scored the highest among the PERMA dimensions, suggesting students’ well-being is drawn more significantly from the perceived purpose and value of their study, rather than from immediate affective experiences or task-based achievements.followed by Relationships and Positive Emotion. In contrast, Engagement and Accomplishment were weaker, suggesting challenges in sustaining focus and achieving learning goals. Scores for Negative Emotion were relatively high overall and displayed high variance, indicating individual differences in emotional regulation. Network analysis revealed that Positive Emotion functioned as the central node, linking strongly with Meaning, Engagement, and Accomplishment. Engagement and Accomplishment formed a tightly coupled pair, while Meaning acted as a bridge supported by Relationships. Negative Emotion remained peripheral, with weak or negative connections, particularly to Positive Emotion. Comparisons between high- and low-progress groups revealed broadly stable global structures; however, low-progress learners exhibited stronger negative links, indicating greater emotional vulnerability. These results extend the application of Positive Psychology to second language acquisition and provide useful information for enhancing Japanese language instruction. Building resilience and achievement, and offering students in emotional distress specific attention, may help improve the overall well-being of learners.